Respuesta :

Answer:

A. y=-2x+3z+25

Step-by-step explanation:

Isolate the term of x and y from one side of the equation.

To solve:

  • The value of y.

[tex]\Longrightarrow: \sf{\sqrt{2x+y-3z}=5}[/tex]

2x+y-3z=25

First, you have to subtract by 2x-3z from both sides.

[tex]\Longrightarrow: \sf{2x+y-3z-\left(2x-3z\right)=25-\left(2x-3z\right)}}[/tex]

Solve.

[tex]\Longrightarrow: \boxed{\sf{y=25-2x+3z}}}[/tex]

  • Therefore, the correct answer is "A. y=-2x+3z+25".

I hope this helps, let me know if you have any questions.

Answer:

Option A

Step-by-step explanation:

Since the "y" variable is inside a root, we need to square both sides of the equation to open the root and solve for y.

When squaring both sides, we get;

[tex]\implies \sqrt{2x + y - 3z} = 5[/tex]

[tex]\implies(\sqrt{2x + y - 3z})^{2} = 5^{2}[/tex]

[tex]\implies2x + y - 3z = 25[/tex]

Now, simply isolate the y-variable to determine its value. This can be done by subtracting 2x on both sides of the equation.

[tex]\implies2x + y - 3z = 25[/tex]

[tex]\implies2x + y - 3z - 2x = 25 - 2x[/tex]

[tex]\implies y - 3z = 25 - 2x[/tex]

Now, add 3z both sides of the equation to further isolate the y-variable.

[tex]\implies y - 3z + 3z = 25 - 2x + 3z[/tex]

[tex]\implies y = 25 - 2x + 3z[/tex]

Therefore, Option A is correct.